Efforts To Increase Understanding Of Pregnant Women Related To Covid-19 Prevention And Distribution Of Mask In Karang Village Temu, Health Center Working Area Of Lingsar District, West Lombok - Nurul Hikmah Annisa (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
The purpose of this research is to find out the efforts to increase under- satnding of pregnant women related to covid-19 prevention and distribution of masks in Karang village temu, health center working area of lingsar district, west lombok. by using a community-based intervention method carried out in Batu Mekar Village, Lingsar District, West Lombok Regency. Efforts to increase understanding of pregnant women about Covid-19 prevention and distribution of masks through classes for pregnant women In Batu Mekar Village, the working area of the Lingsar Health Center, the results were that pregnant women understood Covid-19 prevention, and understood the benefits and how to use masks.